Transbronchial biopsy is useful in predicting UIP pattern - Tomassetti Sara; Cavazza Alberto; Colby Thomas V; Ryu Jay H; Nanni Oriana; Scarpi E; Tantalocco Paola; Buccioli Matteo; Dubini Alessandra; Piciucchi Sara; Ravaglia Claudia; Gurioli Christian; et al. (Respiratory Research, 2012)
Abstract Background Usual interstitial pneumonia (UIP), is a necessary feature pathologically or radiologically for the diagnosis of idiopathic pulmonary fibrosis (IPF). The predictive value of transbronchial biopsy (TBB) in identifying UIP is currently unknown. The objective of this study is to assess the accuracy with which histopathologic criteria of usual interstitial pneumonia (UIP) can be identified in transbronchial biopsy (TBB) and to assess the usefulness of TBBx in predicting a the diagnosis of UIP pattern. We conducted a retrospective blinded and controlled analysis of TBB specimens from 40 established cases of UIP and 24 non-UIP interstitial lung diseases. Results Adequate TBB specimens were available in 34 UIP cases (85% of all UIP cases). TBB contained histopathologic criteria to suggest a UIP pattern (ie. at least one of three pathologic features of UIP present; patchy interstitial fibrosis, fibroblast foci, honeycomb changes) in 12 cases (30% of all UIP cases). Sensitivity, specificity, positive and negative predictive values for the two pathologists were 30% (12/40), 100% (24/24), 100% (12/12), 46% (24/52) and 30% (12/40), 92% (22/24), 86% (12/14), 55% (22/40) respectively. Kappa coefficient of agreement between pathologists was good (0.61, 95% CI 0.31-0.91). The likelihood of identifying UIP on TBB increased with the number and size of the TBB specimens. Conclusion Although sensitivity is low our data suggest that even modest amount of patchy interstitial fibrosis, fibroblast foci, honeycomb changes detected on TBB can be highly predictive of a UIP pattern. Conversely, the absence of UIP histopathologic criteria on TBB does not rule out UIP.